Backwards Design or looking Sideways? Knowledge Translation in the Real World; Comment on "A Call for a Backward Design to Knowledge Translation" - Sarah Bowen; Ian D. Graham (Kerman University of Medical Sciences, 2015)
El-Jardali and Fadllallah provide an excellent summary of the many dimensions of knowledge use, and the breath of issues and activities that must be considered if knowledge is to be put into practice. However, reliance on a continuum (rather than a cyclical, multidirectional, systems) model creates a number of limitations, particularly when promoting evidence-informed action in the areas of health policy and management, where diverse forms of knowledge must be synthesized and decisions made in a rapidly evolving context. We propose a paradigm shift - from viewing Knowledge Translation (KT) as a linear 'knowledge transfer' activity, to a commitment to full stakeholder engagement in knowledge production, dissemination and implementation